Use of non-invasive neurostimulation for rehabilitation in functional movement disorders - Grippe, Talyta; Desai, Naaz; Arora, Tarun; Chen, Robert (Frontiers in Rehabilitation Sciences, 2022)
Functional movement disorders (FMD) are a subtype of functional neurological disorders which involve abnormal movements and include multiple phenomenologies. There is a growing interest in the mechanism, diagnosis, and treatment of these disorders. Most of the current therapeutic approaches rely on psychotherapy and physiotherapy conducted by a multidisciplinary team. Although this approach has shown good results in some cases, FMD cause a great burden on the health system and other treatment strategies are urgently needed. In this review, we summarize past studies that have applied non-invasive neurostimulation techniques, such as transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS) and peripheral nerve stimulation as a treatment for FMD. There is an increasing number of studies related to TMS including randomized controlled trials; however, the protocols amongst studies are not standardized. There is only preliminary evidence for the efficacy of non-invasive neuromodulation in reducing FMD symptoms, and further studies are needed. There is insufficient evidence to allow implementation of these techniques in clinical practice.